Improving the Patient Experience With Migraine Camp, a One‐Day Group Intervention for Adolescents With Chronic Headache and Their Parents. Issue 8 (5th June 2019) - Hall, Amanda L.; Karvounides, Dina; Gelfand, Amy A.; Mankin, Haley; Kessel, Shirley; Corroo, Janet; Malavolta, Carrie P.; Pezzuto, Tara; Chadehumbe, Madeline; Szperka, Christina L.
Abstract : Though chronic migraine is actually common in adolescents, living with constant headache can be isolating for both patients and their families. As an outgrowth of clinical care, we developed the Miles for Migraine Youth Camp, a recurring 1‐day event for adolescents with chronic headache and their parents. Migraine Camp was developed to provide expanded headache education, teach coping strategies for living with chronic pain, and encourage development of a supportive community for adolescents living with chronic headache disorders and their families. The creation and curriculum of the Camps at the University of California San Francisco and Children's Hospital of Philadelphia are described in this manuscript, along with patient and caregiver feedback. Overall, feedback was positive. Teens reported feeling less isolated and more prepared to cope with headaches using new strategies. Both patients and caregivers consistently described benefit from connecting with others who experience similar challenges. The Migraine Camp teams at both institutions found it feasible to conduct the Camps 1‐2 times per year using existing resources, but noted that to scale it to a more regular event additional administrative and/or volunteer support would be needed. In summary, the experience has been positive for patients, caregivers, and staff, and we hope that this manuscript can serve as a "how to" model for similar events at other institutions.